(This post is mostly intended for my own reference, as I found myself repeatedly looking up several conversions between polynomial bases on various occasions.)

Let {\mathrm{Poly}_{\leq n}} denote the vector space of polynomials {P:{\bf R} \rightarrow {\bf R}} of one variable {x} with real coefficients of degree at most {n}. This is a vector space of dimension {n+1}, and the sequence of these spaces form a filtration:

\displaystyle  \mathrm{Poly}_{\leq 0} \subset \mathrm{Poly}_{\leq 1} \subset \mathrm{Poly}_{\leq 2} \subset \dots

A standard basis for these vector spaces are given by the monomials {x^0, x^1, x^2, \dots}: every polynomial {P(x)} in {\mathrm{Poly}_{\leq n}} can be expressed uniquely as a linear combination of the first {n+1} monomials {x^0, x^1, \dots, x^n}. More generally, if one has any sequence {Q_0(x), Q_1(x), Q_2(x)} of polynomials, with each {Q_n} of degree exactly {n}, then an easy induction shows that {Q_0(x),\dots,Q_n(x)} forms a basis for {\mathrm{Poly}_{\leq n}}.

In particular, if we have two such sequences {Q_0(x), Q_1(x), Q_2(x),\dots} and {R_0(x), R_1(x), R_2(x), \dots} of polynomials, with each {Q_n} of degree {n} and each {R_k} of degree {k}, then {Q_n} must be expressible uniquely as a linear combination of the polynomials {R_0,R_1,\dots,R_n}, thus we have an identity of the form

\displaystyle  Q_n(x) = \sum_{k=0}^n c_{QR}(n,k) R_k(x)

for some change of basis coefficients {c_{QR}(n,k) \in {\bf R}}. These coefficients describe how to convert a polynomial expressed in the {Q_n} basis into a polynomial expressed in the {R_k} basis.

Many standard combinatorial quantities {c(n,k)} involving two natural numbers {0 \leq k \leq n} can be interpreted as such change of basis coefficients. The most familiar example are the binomial coefficients {\binom{n}{k}}, which measures the conversion from the shifted monomial basis {(x+1)^n} to the monomial basis {x^k}, thanks to (a special case of) the binomial formula:

\displaystyle  (x+1)^n = \sum_{k=0}^n \binom{n}{k} x^k,

thus for instance

\displaystyle  (x+1)^3 = \binom{3}{0} x^0 + \binom{3}{1} x^1 + \binom{3}{2} x^2 + \binom{3}{3} x^3

\displaystyle  = 1 + 3x + 3x^2 + x^3.

More generally, for any shift {h}, the conversion from {(x+h)^n} to {x^k} is measured by the coefficients {h^{n-k} \binom{n}{k}}, thanks to the general case of the binomial formula.

But there are other bases of interest too. For instance if one uses the falling factorial basis

\displaystyle  (x)_n := x (x-1) \dots (x-n+1)

then the conversion from falling factorials to monomials is given by the Stirling numbers of the first kind {s(n,k)}:

\displaystyle  (x)_n = \sum_{k=0}^n s(n,k) x^k,

thus for instance

\displaystyle  (x)_3 = s(3,0) x^0 + s(3,1) x^1 + s(3,2) x^2 + s(3,3) x^3

\displaystyle  = 0 + 2 x - 3x^2 + x^3

and the conversion back is given by the Stirling numbers of the second kind {S(n,k)}:

\displaystyle  x^n = \sum_{k=0}^n S(n,k) (x)_k

thus for instance

\displaystyle  x^3 = S(3,0) (x)_0 + S(3,1) (x)_1 + S(3,2) (x)_2 + S(3,3) (x)_3

\displaystyle  = 0 + x + 3 x(x-1) + x(x-1)(x-2).

If one uses the binomial functions {\binom{x}{n} = \frac{1}{n!} (x)_n} as a basis instead of the falling factorials, one of course can rewrite these conversions as

\displaystyle  \binom{x}{n} = \sum_{k=0}^n \frac{1}{n!} s(n,k) x^k

and

\displaystyle  x^n = \sum_{k=0}^n k! S(n,k) \binom{x}{k}

thus for instance

\displaystyle  \binom{x}{3} = 0 + \frac{1}{3} x - \frac{1}{2} x^2 + \frac{1}{6} x^3

and

\displaystyle  x^3 = 0 + \binom{x}{1} + 6 \binom{x}{2} + 6 \binom{x}{3}.

As a slight variant, if one instead uses rising factorials

\displaystyle  (x)^n := x (x+1) \dots (x+n-1)

then the conversion to monomials yields the unsigned Stirling numbers {|s(n,k)|} of the first kind:

\displaystyle  (x)^n = \sum_{k=0}^n |s(n,k)| x^k

thus for instance

\displaystyle  (x)^3 = 0 + 2x + 3x^2 + x^3.

One final basis comes from the polylogarithm functions

\displaystyle  \mathrm{Li}_{-n}(x) := \sum_{j=1}^\infty j^n x^j.

For instance one has

\displaystyle  \mathrm{Li}_1(x) = -\log(1-x)

\displaystyle  \mathrm{Li}_0(x) = \frac{x}{1-x}

\displaystyle  \mathrm{Li}_{-1}(x) = \frac{x}{(1-x)^2}

\displaystyle  \mathrm{Li}_{-2}(x) = \frac{x}{(1-x)^3} (1+x)

\displaystyle  \mathrm{Li}_{-3}(x) = \frac{x}{(1-x)^4} (1+4x+x^2)

\displaystyle  \mathrm{Li}_{-4}(x) = \frac{x}{(1-x)^5} (1+11x+11x^2+x^3)

and more generally one has

\displaystyle  \mathrm{Li}_{-n-1}(x) = \frac{x}{(1-x)^{n+2}} E_n(x)

for all natural numbers {n} and some polynomial {E_n} of degree {n} (the Eulerian polynomials), which when converted to the monomial basis yields the (shifted) Eulerian numbers

\displaystyle  E_n(x) = \sum_{k=0}^n A(n+1,k) x^k.

For instance

\displaystyle  E_3(x) = A(4,0) x^0 + A(4,1) x^1 + A(4,2) x^2 + A(4,3) x^3

\displaystyle  = 1 + 11x + 11x^2 + x^3.

These particular coefficients also have useful combinatorial interpretations. For instance:

  • The binomial coefficient {\binom{n}{k}} is of course the number of {k}-element subsets of {\{1,\dots,n\}}.
  • The unsigned Stirling numbers {|s(n,k)|} of the first kind are the number of permutations of {\{1,\dots,n\}} with exactly {k} cycles. The signed Stirling numbers {s(n,k)} are then given by the formula {s(n,k) = (-1)^{n-k} |s(n,k)|}.
  • The Stirling numbers {S(n,k)} of the second kind are the number of ways to partition {\{1,\dots,n\}} into {k} non-empty subsets.
  • The Eulerian numbers {A(n,k)} are the number of permutations of {\{1,\dots,n\}} with exactly {k} ascents.

These coefficients behave similarly to each other in several ways. For instance, the binomial coefficients {\binom{n}{k}} obey the well known Pascal identity

\displaystyle  \binom{n+1}{k} = \binom{n}{k} + \binom{n}{k-1}

(with the convention that {\binom{n}{k}} vanishes outside of the range {0 \leq k \leq n}). In a similar spirit, the unsigned Stirling numbers {|s(n,k)|} of the first kind obey the identity

\displaystyle  |s(n+1,k)| = n |s(n,k)| + |s(n,k-1)|

and the signed counterparts {s(n,k)} obey the identity

\displaystyle  s(n+1,k) = -n s(n,k) + s(n,k-1).

The Stirling numbers of the second kind {S(n,k)} obey the identity

\displaystyle  S(n+1,k) = k S(n,k) + S(n,k-1)

and the Eulerian numbers {A(n,k)} obey the identity

\displaystyle  A(n+1,k) = (k+1) A(n,k) + (n-k+1) A(n,k-1).